Exploring the importance of pooling schemes for convolutional neural networks in hiragana character classification - Osuna Medrano, Héctor; Moroyoqui Olan, Marcos Alberto; Espina Lopez, David; Orozco Rosas, Ulises; Picos, Kenia (My University, 2022)
This paper presents a comparison between the implementation of different convolutional neural varying the usage of pooling layers to address the problem of hiragana character classification. This study is focused on understanding how the selection and usage of different pooling layers affect the accuracy convergence in a model. To assess this situation eight models were tested with different configurations and using minimum pooling, average pooling, and max pooling schemes. Experimental results to validate the analysis and implementation are provided. RESUMEN Este artículo presenta una comparación entre la implementación de diferentes modelos de redes neuronales convolucionales que varían el uso de capas de agrupación para abordar el problema de la clasificación de caracteres hiragana. Este estudio se centra en comprender cómo la selección y el uso de diferentes capas de agrupación afectan la convergencia de precisión en un modelo. Para evaluar esta situación, se probaron ocho modelos con diferentes configuraciones y utilizando esquemas de agrupación mínima, agrupación media y agrupación máxima. Se proporcionan resultados experimentales para validar el análisis y la implementación.
SPIE. Digital Library
Proceedings Volume 12225, Optics and Photonics for Information Processing XVI; 122250C (2022)
Keywords: Network models; Pooling schemes; Analysis; Campus Tijuana